2017
DOI: 10.1016/j.apnum.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Shannon wavelet inverse Fourier technique for pricing European options

Abstract: The SWIFT method for pricing European-style options on one underlying asset was recently published and presented as an accurate, robust and highly efficient technique. The purpose of this paper is to extend the method to higher dimensions by pricing exotic option contracts, called rainbow options, whose payoff depends on multiple assets. The multidimensional extension inherits the properties of the one-dimensional method, being the exponential convergence one of them. Thanks to the nature of local Shannon wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This paper aims to further extend the applicabilities of these state-of-the-art numerical integration methods to the above-mentioned general jump-diffusion FX model. We use the SWIFT method, due to the established robustness of Shannon wavelets in option pricing, as demonstrated in a number of works, such as Colldeforns-Papiol et al (2017); Maree et al (2017); Ortiz-Gracia and Oosterlee (2016). The proposed SWIFT-based method is developed within the hybrid MC-PDE computational framework put forward in Dang et al (2015bDang et al ( , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to further extend the applicabilities of these state-of-the-art numerical integration methods to the above-mentioned general jump-diffusion FX model. We use the SWIFT method, due to the established robustness of Shannon wavelets in option pricing, as demonstrated in a number of works, such as Colldeforns-Papiol et al (2017); Maree et al (2017); Ortiz-Gracia and Oosterlee (2016). The proposed SWIFT-based method is developed within the hybrid MC-PDE computational framework put forward in Dang et al (2015bDang et al ( , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the characteristic function is used to recover the series expansion coefficients of the density. SWIFT has already been successfully applied to European options with one and two underlying assets in [13] and [14] respectively, as well as to earlyexercise and discrete barrier options in [15]. It has been shown that among the strengths of SWIFT method is the a priori knowledge of the scale of approximation and equivalently the number of terms in the expansion.…”
Section: Introductionmentioning
confidence: 99%